Pholcus mixiaoqii sp. nov., one new spider species from Tibet, China (Araneae: Pholcidae) - Xu, Hao; Zhang, Chuntian; Yao, Zhiyuan (Zootaxa, 2019)
The genus Pholcus Walckenaer, 1805 belongs to the family Pholcidae C.L. Koch, 1850, which is a species-rich group, including 94 genera and 1,716 species (World Spider Catalog 2019). Pholcus is mainly distributed in the Palaearctic, Indo-Malayan, Afrotropical, and Australasian Region (Huber 2011). The only exception is the Pholcus kingi group with ten species in the southeastern USA (Huber 2011). The genus includes species from a wide range of habitats, e.g., between buttresses, in small holes or caves, among and under large rocks, or on the underside of green leaves (Huber 2011). Many taxonomic changes were implemented on the latest molecular phylogeny analyses (Eberle et al. 2018; Huber et al. 2018), including nine new genera resulted from splitting Pholcus: Cantikus Huber, 2018, Kelabita Huber, 2018, Kintaqa Huber, 2018, Meraha Huber, 2018, Muruta Huber, 2018, Paiwana Huber, 2018, Pribumia Huber, 2018, Teranga Huber, 2018, and Tissahamia Huber, 2018. The genus Sihala Huber, 2011 was synonymized with Pholcus and the species Pholcus agadir Huber, 2011 was moved to Micropholcus Deeleman-Reinhold & Prinsen, 1987 (Huber et al. 2018). Nevertheless, Pholcus continues to be the most species-rich genus in Pholcidae and currently includes 328 species belonging to 21 species-groups [previously: 393 species and 32 species-groups] (Huber 2011; Huber et al. 2018; World Spider Catalog 2019). One of the generic species-groups, the Pholcus nenjukovi species-group, contains eight species and occurs in northeastern Iran, Afghanistan, Tajikistan, and Russia (the single record of Pholcus sidorenkoi Dunin, 1994 from Russia is dubious, see Huber 2011: 339). In the present study, we describe a new species from southwestern Tibet, China assigned to the Pholcus nenjukovi species-group. This distribution represents the eastern most record for the species-group (Fig. 1).